A Dosimetric Study on Slab-pinewood-slab Phantom for Developing the Heterogeneous Chest Phantom Mimicking Actual Human Chest - Gurjar, Om Prakash (J Med Phys, 2017)
The aim is to study the density, isodose depths, and doses at different points in slab-pinewood-slab (SPS) phantom, solid phantom SP34 (made up of polystyrene), and chest level of actual patient for developing heterogeneous chest phantom mimicking thoracic region of human body. A 6 MV photon beam of field size of 10 cm × 10 cm was directed perpendicular to the surface of computed tomography (CT) images of chest level of patient, SPS phantom, and SP34 phantom. Dose was calculated using anisotropic analytical algorithm. Hounsfield units were used to calculate the density of each medium. Isodose depths in all the three sets of CT images were measured. Variations between planned doses on treatment planning system (TPS) and measured on linear accelerator (LA) were calculated for three points, namely, near slab–pinewood interfaces (6 and 18 cm depths) and 10 cm depth in SPS phantom and at the same depths in SP34 phantom. Density of pinewood, SP34 slabs, chest wall, lung, and soft tissue behind lung was measured as 0.329 ± 0.08, 0.999 ± 0.02, 0.898 ± 0.02, 0.291 ± 0.12, and 1.002 ± 0.03 g/cc, respectively. Depths of 100% and 90% isodose curves in all the three sets of CT images were found to be similar. Depths of 80%, 70%, 60%, 50%, and 40% isodose lines in SPS phantom images were found to be equivalent to that in chest images, while it was least in SP34 phantom images. Variations in doses calculated at 6, 10, and 18 cm depths on TPS and measured on LA were found to be 0.36%, 1.65%, and 2.23%, respectively, in case of SPS phantom, while 0.24%, 0.90%, and 0.93%, respectively, in case of SP34 slab phantom. SPS phantom seemed equivalent to the chest level of human body. Dosimetric results of this study indicate that patient-specific quality assurance can be done using chest phantom mimicking thoracic region of human body, which has been fabricated using polystyrene and pinewood.